(untitled) (Journal of Economic Research & Business Administration, 2016)
Commercialization and usage of domestic scientific research results are very important in the formation of an innovative economy. In this regard, it should be noted that effective operation of innovation infrastructure facilities, and especially offices and centers of commercialization are necessary. When the “National Agency for Technological Development» of Kazakhstan stopped funding commercialization offices, many of them either cut staff or stopped their work. However, after the adoption of a new law in 2015, commercialization has become one of the priorities of the universities and research institutes. Therefore, the question about how to effectively organize the work of the newly created office of commercialization arises. This article discusses world experience in the organization of the offices and centers of commercialization. Also, the main functions of the office of commercialization, income distribution mechanism, and the requirements for personnel and indicators to assess performance were analyzed. The article may be of interest to those involved in the commercialization of scientific research in universities.